ANALISIS KELAYAKAN PENINGKATAN PRODUKSI DI INDUSTRI EGG ROLL UBI UNGU âSHASA" - , ANGGRAENI PUSPITA D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of production facilities in the Industrial Egg Roll Sweet Purple \"SHASA\" done by reviewing the financial aspects. Feasibility analysis is done to determine the financial feasibility of investment in egg roll making machine Industry Egg Roll Sweet Purple \"Shasa\". The analysis of the financial feasibility criteria performed using NPV (Net Present Value), IRR (Internal Rate of Return) and BEP (Break Even Point). Based on the analysis of financial investments egg roll making machine is feasible to implement in Industrial Egg Roll Sweet Purple \"Shasa\" with the results of the NPV (Rp 2.399.066.717,08) IRR (50%) and BEP (BEP time of 0.20 months: BEP 16 251 units box egg roll and BEP rupiah Rp 146.246.344) From the results of the sensitivity analysis, that the egg roll making machine investment is not sensitive to the increase or decrease in revenue from the sale of the egg roll.